Literature Study: A Blended Learning Model in Improving Creative Thinking Ability - Laeny Siti Hasanah (JLER (Journal of Language Education Research), 2023)
The selection of learning models is one of the important components that can affect the effectiveness of the learning process as well as the quality and learning outcomes. The blended learning model is known to be able to overcome various limitations associated with online learning and face-to-face teaching. Blended learning is also a combination of face-to-face teaching and online teaching, involving teachers, pictures, videos, digital assignments and face-to-face discussions. Learning with the blended learning model can be applied to every student and can be accessed anytime and anywhere via the internet. The Blended Learning Learning Model is considered very effective because the interaction of teachers and students is not limited by space and time and is able to overcome problems in the learning process. This study uses a qualitative approach with a literature study method. The data analysis technique used is content analysis. The results of this study conclude that the innovation of the Blended Learning learning model will raise students' independence and self-confidence because they try to find and explore learning resources not only from the teacher.